2018
DOI: 10.4103/ijpsym.ijpsym_141_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Phantom Ringing and Phantom Vibration among Medical Interns and their Relationship with Smartphone Use and Perceived Stress

Abstract: Background: Phantom sensations like phantom vibration (PV) and phantom ringing (PR)— the sensations of vibration and ringing of the phone when they are not, respectively—are among the latest in the category of “techno-pathology” to receive global attention. This study was conducted with the aim to estimate the prevalence of such sensations among medical interns and their association with perceived stress levels and smartphone usage pattern. Materials and Methods: Ninety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…This frequency of smartphone addiction is higher than the range (39% to 44%) found in the Indian population by a meta-analysis of six Indian studies in 2014 and recent studies in medical students. [6,12,13] This study found no significant gender differences in addiction as opposed to the higher smartphone addiction in female students observed by authors in Korea and the Middle-East. [29][30][31] Similar to our study, no significant gender difference was observed by Basu et al in medical students in India.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…This frequency of smartphone addiction is higher than the range (39% to 44%) found in the Indian population by a meta-analysis of six Indian studies in 2014 and recent studies in medical students. [6,12,13] This study found no significant gender differences in addiction as opposed to the higher smartphone addiction in female students observed by authors in Korea and the Middle-East. [29][30][31] Similar to our study, no significant gender difference was observed by Basu et al in medical students in India.…”
Section: Discussioncontrasting
confidence: 67%
“…The positive correlation between PSS and SAS-SV scores in our study was higher than the correlation of r = 0.30 reported in another study in medical students in Maharashtra. [13] Samaha et al used similar scales and scoring systems and found an association between smartphone addiction and perceived stress, while another Romanian study reiterated these findings, albeit with different scales of measurement. [34,35] Smartphone addiction provides an escape from reality and could be hypothesized to be a mechanism adopted by students to alleviate stress, but further studies are required in this regard.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…3 Studies in medical students in Jammu and Kashmir, Delhi, and Maharashtra have found a high prevalence of smartphone addiction, ranging from 34% to 40%. [4][5][6][7] According to the WHO, this increase in use is associated not only with clear and tremendous benefits to the users and societies, but also with documented cases of excessive use which often have negative health consequences. Thus, gaming disorder was introduced as a new condition in the 11th revision of the International Classification of Diseases (ICD-11) which includes health concerns like insufficient physical activity, unhealthy diet, problems with eyesight or hearing, musculoskeletal problems, sleep deprivation, and associated health conditions such as depression and venous thromboembolism.…”
Section: Introductionmentioning
confidence: 99%